Improving the Defect Tolerance of PBF‐LB/M Processed 316L Steel by Increasing the Nitrogen Content. Issue 1 (2nd August 2022) - Stern, Felix; Becker, Louis; Cui, Chengsong; Tenkamp, Jochen; Uhlenwinkel, Volker; Steinbacher, Matthias; Boes, Johannes; Lentz, Jonathan; Fechte-Heinen, Rainer; Weber, Sebastian; Walther, Frank
Abstract : Nitrogen (N) in steels can improve their mechanical strength by solid solution strengthening. Processing N‐alloyed steels with additive manufacturing, here laser powder bed fusion (PBF‐LB), is challenging as the N‐solubility in the melt can be exceeded. This degassing of N counteracts its intended positive effects. Herein, the PBF‐LB processed 316L stainless steel with increased N‐content is investigated and compared to PBF‐LB 316L with conventional N‐content. The N is introduced into the steel by nitriding the powder and mixing it with the starting powder to achieve an N‐content of approximately 0.16 mass%. Thermodynamic calculations for maximum solubility to avoid N outgassing and pore formation under PBF‐LB conditions are performed beforehand. Based on the results, a higher defect tolerance under fatigue characterized by Murakami model can be achieved without negatively influencing the PBF‐LB processability of the 316L steel. The increased N‐content leads to higher hardness (+14%), yield strength (+16%), tensile strength (+9%), and higher failure stress in short time fatigue test (+16%). Abstract : An austenitic stainless steel powder is nitrided to improve the defect tolerance of PBF‐LB/M processed parts. The nitrogen content is tuned to not exceed the nitrogen solubility during the process. Whereas quasistatic strength is visibly improved, a fracture mechanical approach is necessary to confirm that also the defect tolerance under fatigue is enhanced.